Permasalahan Pengelolaan Sampah Desa Tegal Sari Kel. Mandala I Medan Denai, Kota Medan - Elsy Nila Sari Situmeang; Khairun Nisa; Ramadhan Fitriani; Meilinda Suriani Harefa; Syukrie Hidayat (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Waste is a problem that often occurs in an area, one of which is the village of Tegal Sari Mandala I. Waste management that is not complex will create a problem for the village and will require innovative solutions to overcome the problem of waste in the village. The aim of this research is to identify waste management issues and the reasons why waste cannot be managed properly by the people of Tegal Sari Village. This research method uses a qualitative approach, sampling is carried out by interviewing information identified according to their identity and problems related to the area studied. Data analysis used in data reduction research, data presentation, and drawing conclusions. The main cause of the waste problem in the village is that the local community's livelihood is scavengers and this causes large piles of rubbish to be piled up by the community, lack of public awareness of managing waste or sorting waste and turning it into a craft with economic value. This research can be used as a guide for villages that have similar problems, by utilizing participatory and innovative waste management in rural areas.